Work-related injuries and stress among iron and steel fabrication workers in Bhubaneswar, Odisha: A cross-sectional study - Parimita, Pragyan; Debata, Ipsita; Nayak, Smrutiranjan; Behera, Basanta Kumar (International Journal of Occupational Safety and Health, 2024)
Introduction: Any personal injury or death due to an occupational accident is classified as an occupational injury by the International Labor Organization. The metal fabrication work in automotive, aerospace, and electronic manufacturing industries can be physically and mentally exhausting. No research is available on work-related injuries and stress among iron and steel fabrication workers in Odisha. This study was conducted to evaluate the prevalence of work-related injuries and the risk factors associated with them. Methods: A cross-sectional study was done from November 2020 to June 2022 in eligible and consenting iron and steel fabrication workers, selected by multistage random sampling. Data was collected by a pretested questionnaire and the Workplace Stress Scale. Data was analyzed using IBM Statistical Package for Social Sciences v23. Descriptives, chi-square test, and logistic regression were used for interpretation. A p-value < 0.05 was considered statistically significant. Results: Out of 386 male workers, the majority (80.83%) were 18-40 years old. Around 76.33% had at least one episode of injury in the past year. Injury to fingers (79.33%) was most common. The most common type was cuts (80.33%) and the major source was hand tools (81%). Marital status, education, occupation, and work conditions were significantly associated with injury (p = 0.001). Around 39.39% had severe stress levels. Conclusion: We identified the hazardous working conditions increasing the risk of injury among workers. Creating awareness regarding safety measures can avert such injuries.